The burnout challenge : managing people's relationships with their jobs - Maslach, Christina; Leiter, Michael P. (Harvard University Press, 2022)
"Solutions to workplace burnout often involve victim-blaming: Stressed? Try therapy-or a new job. But burnout is a sign of defective workplaces, not workers. Drawing on decades of research, Christina Maslach and Michael Leiter show managers how to recognize burnout and fix problems cost-effectively, improving employees' productivity and health"--